2012
DOI: 10.1002/asna.201211727
|View full text |Cite
|
Sign up to set email alerts
|

Gregor@night: The future high‐resolution stellar spectrograph for the GREGOR solar telescope

Abstract: We describe the future night-time spectrograph for the GREGOR solar telescope and present its science core projects. The spectrograph provides a 3-pixel resolution of up to R = 87 000 in 45échelle orders covering the wavelength range 390-900 nm with three grating settings. An iodine cell can be used for high-precision radial velocity work in the 500-630 nm range. The operation of the spectrograph and the telescope will be fully automated without the presence of humans during night-time and will be based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been shown that the GREGOR solar telescope is capable of unattended night-time operation as required for Gre-gor@night (Strassmeier et al 2012) by assessing its capability to point to any position within the entire reachable sky with remarkable accuracy. Alignment problems of the coudé train are suggested by the results of the pointing campaign, but should be clarified further by measuring the (differential) pointing model at the coudé focus and with the piggy-back telescope simultaneously rather than sequentially.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the GREGOR solar telescope is capable of unattended night-time operation as required for Gre-gor@night (Strassmeier et al 2012) by assessing its capability to point to any position within the entire reachable sky with remarkable accuracy. Alignment problems of the coudé train are suggested by the results of the pointing campaign, but should be clarified further by measuring the (differential) pointing model at the coudé focus and with the piggy-back telescope simultaneously rather than sequentially.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a spectrograph for stellar activity studies and the search for solar twins expand the scientific usage of the GREGOR telescope to the nighttime domain. 24 The GREGOR telescope replaced the 45-cm Gregory-Coudé Telescope, which had been operated on Tenerife since 1985. The construction of the new telescope was carried out by a consortium of several German institutes, namely, the Kiepenheuer-Institut für Sonnenphysik Freiburg, the Leibniz-Institut für Astrophysik Potsdam (AIP), and the Institut für Astrophysik Göttingen.…”
Section: Gregor Solar Telescopementioning
confidence: 99%